IMPROVING TIME AND COST ESTIMATION OF WEST WANAGON SLOPE STABILITY PROJECT IN GRASBERG SURFACE MINE CLOSURE: A FUZZY LOGIC AND PROGRAM EVALUATION AND REVIEW TECHNIQUE (PERT) INTEGRATION APPROACH - Gino Simanjuntak, Maychel
Accurate time and cost estimation is critical in the successful closure of large-scale mining projects such as the West Wanagon Slope Stability Project at the Grasberg Surface Mine. Historically, these estimations have been marked by inaccuracies, which have negatively affected the overall efficiency and effectiveness of the projects. This study specifically addresses the enduring issues of time and cost estimation inaccuracies within PT Freeport Indonesia's closure projects. By employing a comprehensive array of analytical techniques including KepnerTregoe Problem Analysis, Critical Path Analysis, PERT Analysis, and an innovative integration of Fuzzy Logic with PERT. The research endeavors to enhance the accuracy of these critical estimations.